Ergonomics principles in the Malay translation of ‘Kitab Ar‐Raḥmah Fī Aṭ‐Ṭibb Wa Al‐Ḥikmah’ - Taib, Ibrahim Adham (2015)
Ergonomics is believed to originate in the West centuries ago. For example, the 17th century Italian physician, Bernadino Ramazzini, is regarded as the father of occupational medicine, and has been credited for associating musculoskeletal disorders with occupation. Nevertheless, what about ergonomics in the Malay Archipelago? This talk discusses the ergonomics principles found in two Malay Medical Manuscripts, which provides evidence that ergonomics were practiced by locals before the 20th century.